Two-Phase Flow CFD Analysis of Temperature Effects on Oil Supplied to Small-Bore Journal Bearing with Oil Supply Groove - Fuma Sakai (Japanese Society of Tribologists, 2018)
Oil whips might present a risk that is associated with bearing seizures. To conveniently suppress oil whips, a stabilization method using starved lubrication has been proposed. As the oil film becomes thinner, an increase in oil film temperature is expected. In this study, the bearing temperature was studied in the cases of oil whip, transition condition, and starved lubrication. Moreover, the temperature distributions in the transition and starved lubrication conditions were studied using a two-phase flow computational fluid dynamics (CFD) analysis. As a result, it was found that the heat amount due to shear friction was small in the case of the transition condition, whereas the temperature inside the bearing was approximately the same as that of the supply oil, from both experimental and analytical perspectives. In the case of the starved lubrication condition, it was found that the air flowing out of the oil supply groove created a circulated flow, which cooled the side end of the bearing, thereby controlling the temperature at the center of the bearing.